Transcriptional programming using engineered systems of transcription factors and genetic architectures - Ronald E. Rondon (Nature Portfolio, 2019)
Successful approaches for controlling gene expression modulate mRNA synthesis by coupling it to inducible transcription effectors. Here the authors design 27 non-natural and non-synonymous transcription factors.